Foreign experience and specific of functioning of corporate associations - Khimchenko, Andriy; Kulish, Olena (Skhid, 2013)
The features of becoming and specific of functioning of corporate associations of the USA, Japan, South Korea and Germany are explored in the article. On the basis of the conducted research signs which are fixed in basis of determination of model of corporate sector are systematized.